A Model for Improving the Quality of Student Internship Placements in Engineering Degrees - Garcia, Rafael; Puig, Jordi (International Journal of Advanced Corporate Learning (iJAC), 2011)
Work Internship Placements (WIP) is a new and transversal enterprise internships programme, which is focused on quality improvement, academic control and satisfaction of collaborating enterprises. This programme is addressed to the engineering students of the Polytechnic School at the University of Girona (UdG) in Spain. The fundamental WIP infrastructure combines a web-based intranet platform, that provides a complete set of WIP tools, with a protocol of procedures and tasks that are observed and followed at all internship stages by every participating agent, i.e. enterprises, students, coaching professors and administrative staff. Our new programme is centered on a broader, more holistic internship placement procedure than the traditional â??career and academic goals